2022
DOI: 10.1186/s13102-022-00495-1
|View full text |Cite
|
Sign up to set email alerts
|

Can MRI knee joint measurements predict the population at risk of ACL injury?

Abstract: Background Anterior cruciate ligament (ACL) injuries have been increasing significantly over time. The relationship between the ACL injury and the knee joint structures is poorly understood. The purpose of this study is to examine whether the measurements of different structures in the knee joint are linked with ACL injury in affected patients. Methods This retrospective case–control study included patients who suffered from ACL tears and underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There have been multiple studies that assess risk factors for ACL graft failure, including lateral tibial slope [ 2 , 3 , 15 , 17 , 23 , 24 , 30 , 32 , 36 , 41 ]. Lachlan et al concluded in their stability study that ligamentous laxity, male sex, posterior third medial or lateral meniscal injury, increased posterior tibial slope, and chronicity were related to a high-grade pivot shift and higher risk for repeated ACL injury [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple studies that assess risk factors for ACL graft failure, including lateral tibial slope [ 2 , 3 , 15 , 17 , 23 , 24 , 30 , 32 , 36 , 41 ]. Lachlan et al concluded in their stability study that ligamentous laxity, male sex, posterior third medial or lateral meniscal injury, increased posterior tibial slope, and chronicity were related to a high-grade pivot shift and higher risk for repeated ACL injury [ 3 ].…”
Section: Discussionmentioning
confidence: 99%